Improvement of intestinal inflammation after treatment with CFTR modulators in cystic fibrosis patients - Ruth García Romero; Concepción López Cárdenes; Elena Crehuá Gaudiza; Marina Álvarez Beltrán; Mercedes Murray Hurtado; Carlos Tutau Gómez; Inés Loverdos Eseverri; Encarni Torcuato Rubio; Camila García Volpe; Enrique Salcedo Lobato; María Medina Martínez; Carmen Martin Fernández; et al. (Anales de Pediatría (English Edition))
Introduction: Treatments with CFTR protein modulators have improved respiratory and digestive health in patients with cystic fibrosis. Objective: To assess changes in intestinal inflammation through the analysis of fecal calprotectin in patients with cystic fibrosis during treatment with CFTR modulators. Material and methods: Prospective multicenter study of changes in fecal calprotectin in patients with cystic fibrosis treated with CFTR modulators, comparing double combinations (lumacaftor/ivacaftor or tezacaftor/ivacaftor) and triple combinations (elexacaftor/tezacaftor/ivacaftor). We collected aata before treatment initiation and at 6 and 12 months. Results: Analysis of 117 patients (69% with F508del/F508del). The median baseline fecal calprotectin level was 49 µg/g (IQR, 23–108); 48.7% had median levels greater than 50 µg/g and 11% levels greater than 250 µg/g. Fecal calprotectin decreased in both groups, with a greater decrease in patients treated with elexacaftor/tezacaftor/ivacaftor. We found a progressive decrease in abnormal values (>50 µg/g) at 6 months (48.7% vs 33.1%; P = .0067) and at 12 months (54% vs 33.5%; P = .0218). In the elexacaftor/tezacaftor/ivacaftor group, only two patients at 6 months and one patient at 12 months had levels greater than 250 µg/g. The estimated change at 12 months in the triple therapy group compared to the other group was −133 µg/g (95% CI, −254 to −13; P = .030); and, adjusting for sex, probiotics and Pseudomonas aeruginosa, −130 µg/g (−259 to −1; P = .049). Conclusions: Treatment with CFTR modulators reduces intestinal inflammation in patients with cystic fibrosis, with a greater decrease in patients treated with triple therapy. Resumen: Introducción: Los tratamientos con moduladores de la proteína CFTR han mejorado la salud respiratoria y digestiva de los pacientes con fibrosis quística. Objetivo: Analizar los cambios en la inflamación intestinal mediante estudio de la calprotectina fecal en pacientes con fibrosis quística durante el tratamiento con moduladores. Material y métodos: Estudio multicéntrico prospectivo de los cambios en la calprotectina fecal de pacientes con fibrosis quística tratados con moduladores, comparando aquellos constituidos por 2 moléculas (lumacaftor/ivacaftor o tezacaftor/ivacaftor), con los de 3 moléculas (elexacaftor/tezacaftor/ivacaftor). Se recogen datos antes de iniciar el tratamiento, a los 6 y a los 12 meses. Resultados: Análisis de 117 pacientes (69% F508del/F508del). Mediana basal de calprotectina fecal 49 mcg/g (RIC 23–108); 48.7% con >50 mcg/g; 11% con >250 mcg/g. Hubo disminución de calprotectina fecal en ambos grupos, siendo mayor en aquellos con elexacaftor/tezacaftor/ivacaftor. Se observó una disminución progresiva de los valores anormales (>50 mcg/g) a los 6 meses 48.7% vs 33,1% (p = 0,0067) y a los 12 meses 54% vs 33,5% (p = 0,0218). En el grupo elexacaftor/tezacaftor/ivacaftor, sólo 2 pacientes a los 6 meses y 1 paciente a los 12 meses, tenían >250 mcg/g. El cambio estimado (IC del 95%) a 12 meses en el grupo con triple terapia en comparación con el otro grupo fue de −133 mcg/g (−254−13, p = 0,030); y ajustado por sexo, probióticos y Pseudomonas aeruginosa de −130 mcg/g (−259 to −1, p = 0,049). Conclusiones: El tratamiento con moduladores CFTR reduce la inflamación intestinal en pacientes con fibrosis quística, siendo la mejoría más destacada en pacientes tratados con la triple terapia.